Corporate Governance, Audit Committee and the Internet Reporting Of Strategic Information by UAE Non-Financial Listed Firms - Mostafa Kamal Hassan (Journal of Accounting and Management Information Systems (JAMIS), 2015)
The study examines the effect of internal governance mechanisms on the Internet Reporting of Strategic Information (IRSI) in an emerging market economy, the United Arab Emirates (UAE) It relies on the agency theory and the innovation diffusion theory to generate testable hypotheses and augment the explanation behind the empirical results. The study applies a multiple regression on a sample of 37 non-financial firms listed on Abu Dhabi and Dubai financial markets to test the association between audit committee, independent non-executive directors, frequency of board meetings, type of external auditor and IRSI while controlling for firm size, level of risk, firm complexity and firm profitability. The empirical findings show that IRSI is positively and significantly associated with audit committee quality, firm size, level of risk and firm complexity. The findings also show that IRSI is negatively and significantly correlated with the frequency of board of directors meetings. These empirical findings assist UAE regulators and international business community with insights concerned with governance-IRSI relationship. The findings also reveal that board directors and members in audit committee may contribute to the diffusion of innovative disclosure practices such as IRSI. The study is one of few studies that combine the agency theory and innovation diffusion theory to examine the relationship between internal governance mechanisms, particularly audit committee, and the IRSI in an emerging market economy such as the UAE.
Keywords: M41; 650; audit committee; governance; agency theory; innovation diffusion theory; online reporting; "strategy" disclosure; UAE